2016
DOI: 10.1111/wre.12213
|View full text |Cite
|
Sign up to set email alerts
|

Does yield loss due to weed competition differ between organic and conventional cropping systems?

Abstract: High weed abundance in organic crops is thought to be a key factor contributing to the greater yield loss in organic as compared with conventional cropping systems. However, even with greater weed densities than conventional systems, some organic systems have yields comparable to conventional systems, suggesting that cropping systems might differ in yield loss due to weed competition. The diversity in soil nutrient resources due to diversity in crop rotations and variable inputs might enhance crop tolerance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…The weak crop stand in RT was naturally a poor competitor against weeds, resulting in high weed biomass production. The confounding factors affecting weed occurrence, and consequently crop yield, were demonstrated in earlier studies (e.g., Benaragama et al 2016;Woźniak and Soroka 2018).…”
Section: Weed Response To Tillagementioning
confidence: 73%
“…The weak crop stand in RT was naturally a poor competitor against weeds, resulting in high weed biomass production. The confounding factors affecting weed occurrence, and consequently crop yield, were demonstrated in earlier studies (e.g., Benaragama et al 2016;Woźniak and Soroka 2018).…”
Section: Weed Response To Tillagementioning
confidence: 73%
“…These authors reported the plasticity of the more tolerant species as submitted to competitions with other plants. Benaragama et al (2016) found an invasive plant population of 40% higher in relation to the conventional organic crop system with a lower production of approximately 50%, showing the necessity of controlling invasive plants in crops.…”
Section: Resultsmentioning
confidence: 95%
“…However, these empirical studies without a theoretical base often conclude with the requirement for more knowledge about what drives the crop-weed interaction in order to recommend general outcomes. A mounting number of studies have been conducted to evaluate how cover crops can influence weed population dynamics by maximizing competition with weeds (Mirsky et al 2013;Den Hollander et al 2007) and, when intercropped, minimize competition with the cash crop while maximizing competition with the weed (Benaragama et al 2016;Hartwig and Amon 2002). In addition, some cover crops with legume species change the soil nitrogen dynamics favouring the crop or some of the weed species with little knowledge to base generalized weed management recommendations.…”
Section: Direct Competition For Resourcesmentioning
confidence: 99%